O‐Benzoyl side‐chain conformations in 2, 3, 4, 6‐tetra‐O‐benzoyl‐β‐d‐galactopyranosyl‐(1→4)‐1, 2, 6‐tri‐O‐benzoyl‐β‐d‐glucopyranose (ethyl acetate solvate) and 1, 2, 4, 6‐tetra‐O‐benzoyl‐β‐d‐glucopyranose (acetone solvate). Issue 2 (25th January 2019) - Turney, Toby; Pan, Qingfeng; Zhang, Wenhui; Oliver, Allen G.; Serianni, Anthony S.
Abstract : The structures of 2, 3, 4, 6‐tetra‐ O ‐benzoyl‐β‐d ‐galactopyranosyl‐(1→4)‐1, 2, 6‐tri‐ O ‐benzoyl‐β‐d ‐glucopyranose (ethyl acetate solvate) and 1, 2, 4, 6‐tetra‐ O ‐benzoyl‐β‐d ‐glucopyranose (acetone solvate) were determined. Conformational analyses on these compared with other known related saccharides are presented. Abstract : The crystal structures of 2, 3, 4, 6‐tetra‐ O ‐benzoyl‐β‐d ‐galactopyranosyl‐(1→4)‐1, 2, 6‐tri‐ O ‐benzoyl‐β‐d ‐glucopyranose ethyl acetate hemisolvate, C61 H50 O18 ·0.5C4 H8 O2, and 1, 2, 4, 6‐tetra‐ O ‐benzoyl‐β‐d ‐glucopyranose acetone monosolvate, C34 H28 O10 ·C3 H6 O, were determined and compared to those of methyl β‐d ‐galactopyranosyl‐(1→4)‐β‐d ‐glucopyranoside (methyl β‐lactoside) and methyl β‐d ‐glucopyranoside hemihydrate, C7 H14 O6 ·0.5H2 O, to evaluate the effects of O ‐benzoylation on bond lengths, bond angles and torsion angles. In general, O ‐benzoylation exerts little effect on exo‐ and endocyclic C—C and endocyclic C—O bond lengths, but exocyclic C—O bonds involved in O ‐benzoylation are lengthened by 0.02–0.04 Å depending on the site of substitution. The conformation of the O ‐benzoyl side‐chains is highly conserved, with the carbonyl O atom either eclipsing the H atom attached to a 2°‐alcoholic C atom or bisecting the H—C—H bond angle of an 1°‐alcoholic C atom. Of the three bonds that determine the side‐chain geometry, the C—O bond involving the alcoholic C atom exhibits greater rotational variability than the remaining C—O and C—C bonds involving the carbonyl C atom. These findings are in good agreement with recent solution NMR studies of the O ‐acetyl side‐chain conformation in saccharides.